Dynamics of pulse propagation with solitary waves in monomode optical fibers with nonlinear Fokas system - Ali, Karmina K.; Tarla, Sibel; Yusuf, Abdullahi; Umar, Huzaifa; Yilmazer, Resat (World Scientific Publ Co Pte Ltd, 2025)
In this study, a unified auxiliary equation method, which is one of the powerful methods for exploring nonlinear model solutions, is used in the Fokas system, with complex functions representing nonlinear pulse propagation in monomode optical fibers. As a result, we get some solutions, including dark-bright, singular, periodic, bright-dark, Jacobi elliptic functions, trigonometric, hyperbolic and exponential ones. In addition, we use a computer program to generate 3D, 2D and counterplot graphics from the obtained solutions by assigning specific values to the involved parameters. While discussing, the graphs for various values of an arbitrary constant are examined. These findings constitute an important step in understanding how solitary waves are generated in nonlinear media. Since the studied model is used in many domains, including Bose-Einstein condensates and plasma physics, these results improve our theoretical knowledge and open up new avenues for potential real-world applications and the development of cutting-edge technologies.
Keywords: Exact solutions; Fokas system; unified auxiliary equation method; Jacobi elliptic functions